2019
DOI: 10.21470/1678-9741-2019-0008
|View full text |Cite
|
Sign up to set email alerts
|

Prosthesis-Patient Mismatch after Surgical Aortic Valve Replacement: Neither Uncommon nor Harmless

Abstract: Prosthesis-patient mismatch (PPM) after surgical aortic valve replacement (SAVR) is an issue that has been overlooked (not to say neglected). Cardiac surgeons must bear in mind that this is a real problem that we must tackle. The purpose of this paper is to be a wake-up call to the surgical community by giving a brief overview of what PPM is, its incidence and impact on the outcomes. We also discuss the increasing role played by imaging for predicting and assessing PPM after SAVR (with which surgeons must beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…1-4-5 It is easy to deduce that patients with SAA who undergo a surgical aortic valve replacement (SAVR) are more likely to receive smaller prostheses, which makes them more predisposed to prosthesis patient-mismatch (PPM). This complication has been found to be associated with increases in perioperative, early-, mid-, and long-term mortality rates, 6,7 which leads to the necessity of implementation of surgical strategies to prevent PPM. Furthermore, worsening this scenario, surgical societies have raised serious concerns regarding inconsistencies in valve size labeling of prosthetic heart valves, 8 which might lead to higher rates of PPM in patients with SAA.…”
Section: Introductionmentioning
confidence: 99%
“…1-4-5 It is easy to deduce that patients with SAA who undergo a surgical aortic valve replacement (SAVR) are more likely to receive smaller prostheses, which makes them more predisposed to prosthesis patient-mismatch (PPM). This complication has been found to be associated with increases in perioperative, early-, mid-, and long-term mortality rates, 6,7 which leads to the necessity of implementation of surgical strategies to prevent PPM. Furthermore, worsening this scenario, surgical societies have raised serious concerns regarding inconsistencies in valve size labeling of prosthetic heart valves, 8 which might lead to higher rates of PPM in patients with SAA.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, an association between both findings with higher morbidity due to higher gradients is possible and likely. Rayol et al (22) reported that PPM is a frequent and relevant hemodynamic complication of SAVR. Surgeons should prospectively calculate the predicted indexed EOA of the prosthesis and patient's body surface area (BSA) and hence plan their surgical procedure adequately; either with an aortic root enlargement (Nikcs-Nunez or Manougian technique) or with a rapid deployment surgical valve to avoid PPM.…”
Section: Follow-up and Outcomementioning
confidence: 99%
“…Patient‐prosthesis mismatch (PPM) is defined as an effective orifice area (EOA) too small for the patient body surface area, mostly resulting in high residual transvalvular pressure gradients 1 . Severe PPM is associated with higher mortality, morbidity, rehospitalization rate, left ventricular workload, and reduced aortic prosthesis longevity 2–4 …”
Section: Introductionmentioning
confidence: 99%
“…1 Severe PPM is associated with higher mortality, morbidity, rehospitalization rate, left ventricular workload, and reduced aortic prosthesis longevity. [2][3][4] The reported prevalence of PPM after surgical aortic valve replacement (SAVR) is high but varies widely in the literature. A large meta-analysis of 34 observational studies and 27,186 patients found a prevalence of 44% (34% moderate PPM and 10% severe PPM).…”
Section: Introductionmentioning
confidence: 99%